Tourist Attractions, Perceived Value, Destination Image, and Loyalty Motivation: A Mediating Variable Analysis - Desy Surya, Elfitra; Afrina Siregar, Nur; Suranta Sinukaban, Dedy (Dinasti Publisher, 2024)
This study examines and analyzes various factors affecting tourist satisfaction and loyalty towards the agro-tourism destination in Tanah Karo. This study utilizes a quantitative research approach with a descriptive methodology to analyze the impact of various factors on tourist loyalty to the agro-tourism destination in Tanah Karo. The research aims to evaluate the effects of tourist attractions, perceived value, destination image, and motivation on tourist loyalty, with satisfaction as a mediating variable. Descriptive analysis will interpret the data, while quantitative analysis will employ statistical tools for hypothesis testing. The study, conducted in Berastagi, Tanah Karo, will use interviews and surveys to collect data from tourists aged 18 to 55 who have visited the destination more than twice. Data will be gathered through questionnaires and secondary sources and analyzed using Structural Equation Modeling with Partial Least Squares. This analysis will include assessing model validity, reliability, and hypothesis testing to understand the direct and indirect effects of the studied variables on tourist loyalty. Based on the research conducted at Agrowisata Tanah Karo, it can be concluded that tourist attractions, perceived value, destination image, and motivation significantly influence tourist satisfaction. Higher satisfaction, in turn, positively impacts tourist loyalty. Specifically, the appeal of tourist attractions and the perceived value contribute to greater satisfaction, which fosters loyalty. Additionally, the destination image and the motivation behind tourists' visits enhance satisfaction and loyalty. Tourist satisfaction mediates the relationship between attractions and loyalty and between perceived value, destination image, and loyalty. Thus, improving these factors can increase tourists' satisfaction and loyalty.